ANTHRAX GLOBAL EPIZOOTOLOGY. 2. DISEASE INCIDENCE IN HUMANS AS INDICATOR OF EPIZOOTIC AND RISK FACTORS - V. V. Makarov; N. Ya. Makhamat (Ветеринария сегодня)
The paper deals with the assessment of the implied associations between the epizootic and epidemic components of the veterinary anthrax epidemiology of animals and humans, as well as with the epidemic risk factors. Analysis of the statistical data for 2007–2017, available in ProMED international database, demonstrated that African, Asian and Near Eastern regions are permanently infected with human anthrax at the incidence rate of 1.0. The disease is very rarely reported in Europe, and it is exotic in the USA and South America. During the study period, the overall incidence amounted to over 3,700 humans: at an average of 340 humans annually ranging from min 81 to max 856. Total mortality amounted to 234 humans with average annual mortality of 21 humans ranging from min 6 to max 58, average annual lethality (patients’ mortality %) – 9.8 ranging from min 3.3 to max 39.5. For the assessment of the genuine interrelation of the incidence in humans and mortality in animals, we compared the statistic samples of the annual infection incidence in a number of the most epidemically and epizootically aﬀected African, Asian and Near Eastern countries as the basic features of the epidemic and epizootic components of the veterinary anthrax epidemiology. The analysis demonstrated no statistical relation between the reported disease incidence in animals and humans. Substantial share of the disease incidence in humans is accounted for unidentifed sources of the infection. Consumption of infected products from domestic (up to 70%) and wild animals prevails among the trivial risk factors of zoonogenous infection in humans, while consumption of meat from domestic animals and contacts with diseased animals prevail among the lethality risk factors. The obtained results are indicative of multiple unidentifed aspects of veterinary anthrax epidemiology.